Elaboration and characterization of a battered food, Frozen from earberry (Solanum melongena). - Zalamea Monina, Luis Felipe; García Choez, Luis Agustín; Maldonado López, Jorge David (Ingeniería Química y Desarrollo, 2022)
The main drawback of  the  eggplant  is  the  rapid  oxidation  caused  by polyphenol oxidase (PPO), comes the need to raise awareness of the different  properties  that  have  this  vegetable  and  benefits  representing consume, its composition is 92% water, it contains minerals among them we can find abundant potassium, iodine and magnesium also has also has vitamin  B1,  vitamin  C,  thiamine,  among  others  and  phytonutrient  as phytosterols and beta carotene. DPPH analysis of which showed a high content of flavonoids being most stands chlorogenic acid, which helps the removal of free radicals in the body was performed. The limiting factor for the development of this research was the production of this vegetable in Ecuador because they are small and sporadic crops near Canton Daule located in the province of Guayas.
Keywords: eggplant; process; batter; characterization; antioxidant; frozen; oxidation